ANALYSIS OF THE CALCULATION ON COST OF PRODUCTION AT NARD SUPPLY COMPANY - Ari Kharisma (Asosiasi Dosen Muda Indonesia, 2024)
The purpose of this study is to analyze the Cost of Good Manufactured (COGM) to determine the selling price of products by comparing calculating of COGM method and Full Cost method that used by Nard Supply. The data used is primary data in the form of interviews, observations, and documentation. The results of this study concluded that the comparison of each method calculated resulted in different COGM. The results of the calculation of COGM using the full cost method resulted in a higher selling price of 69,358 IDR. The company's calculation result is 56,136 IDR. Then a difference of 13,222 IDR is obtained. Based on COGM obtained, it can be concluded that the calculation of the COGM using the full cost method is better than the company's calculation.